The business case for supporting carers: A case study from Hertfordshire. (April 2014) - Rignell, Hannah; Pickup, Sarah
<x content-type="archive" xml:space="preserve">Abstract</x> In March 2012, Hertfordshire County Council approved funding of approximately £100 000 to implement a carer-friendly community and a carer-friendly hospital. The aim of the pilots is to test the impact of a carer friendly health and social care system on permanent admissions to residential care, as well as potential savings to the NHS. The business case was based on keeping eight more carers caring for 1 year by improving multi-agency support for those carers, and their cared for. The carer friendly communities themselves are based on a focussed implementation of the Hertfordshire Commitment to Carers, also known as the 'core offer'; this is what all carers should be entitled to, wherever they happen to hit the system. The business case on which the decision to take forward this work was based provides the core content for this study. The aim was to use real evidence to support concerted action in an area where there is much debate but where justifying additional investment is challenging especially in the current economic climate.